Análise da Sazonalidade e da Tendência de longo prazo na vazão dos Principais Tributários do Rio Paraná Localizados - Conceição, Ana Flávia; Wikuats, Caroline; Capucim, Maurício; Martins, Leila; Martins, Jorge; Brand, Veronika (Ciência e Natura, 2013)
This study analyzed streamflow series for the major left side tributaries of the Paraná River in Brazil. The results suggest that there is agreement regarding the increase in the flow of the rivers analyzed, but increasing rates are not uniform and there are different trends among the rivers when monthly averages maximum and minimum streamflow are considered.